PENYULUHAN TENTANG MEMBANGUN PRIBADI YANG BERKARAKTER BAGI PELAJAR MA'HAD AL-ZAYTUN - Abdur Rahim; Muthia Nur Afifah; Rizal Adrian; Wawan Wawan; Nur Asyifa; Yuliadi Yuliadi; Supriyatno Supriyatno; Saiman Saiman (Jurnal Abdimas Bina Bangsa, 2024)
Counseling on building personal character for Ma'had Al-Zaytun students aims to guide and inspire students in developing strong and authoritative personalities. This counseling aims to provide an in-depth understanding of Islamic moral, ethical and leadership values. Through various interactive learning methods, students will be invited to explore their potential, understand Islamic values, and apply tolerance and diversity. The conclusion from this outreach activity is that Ma'had Al-Zaytun really prioritizes character building because it is an integral part of his students' education. Teachers are a key factor in this process. In building strong character, this includes daily activities such as congregational prayers, reading the Koran, and living clean as efforts that support character formation. Overall, Ma'had Al-Zaytun is committed to forming students' personalities to have strong, good and moral character through holistic education, teacher guidance, and emphasized religious values ​​in everyday life